Human Resource and Financial Management Strategies of Hospitals in Collaboration with BPJS (A Systematic Literature Review) - Maria Vita Widiyaningsih; Muhammad Rakha Gustiawan; Purwadhi; Yani Restiani Widjaja (STMIK Indonesia Banda Aceh, 2025)
This study is a systematic literature review of 25 studies discussing hospital management in Indonesia during the National Health Insurance (JKN) era and collaboration with the Social Security Administering Body (BPJS) Health. The focus of the review includes financial management, human resource management (HRM), business strategies, service quality, and claim issues. The synthesis of results shows that in the financial aspect, cost efficiency strategies, receivables optimization, and service diversification contribute to increased revenue and cash flow stability; however, discrepancies in INA-CBGs tariffs increase the risk of bankruptcy, especially for small hospitals. In the HRM aspect, continuous training, transformational leadership, and adaptation to BPJS regulations have proven to reduce patient complaints and improve employee performance. The implementation of JKN has increased patient volume and service accessibility but has pressured profit margins and revenue per patient. Effective business strategies include service diversification, innovation, process digitalization, and strengthening partnerships with BPJS. The main challenges lie in claim issues due to incomplete documentation, slow verification, and differences in diagnosis codes, which negatively affect hospital cash flow. This review confirms that the integration of financial and HRM management, supported by integrated information technology, is key to the sustainability of hospital operations in the JKN era.